2022
DOI: 10.37766/inplasy2022.9.0118
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with amyotrophic lateral sclerosis: a protocol for systematic review and meta-analysis

Abstract: Review question / Objective: To identify and list the risk factors associated with the onset and progression of ALS. Condition being studied: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder affecting the upper and lower motor neurons in the spinal bulb, cerebral cortex, and spinal cord. The clinical processing symptoms accompany muscle atrophy, fasciculation, and fatigue of limbs, which can lead to general paralysis and death from respiratory failure within 3-5 years after the onset of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[74] Previous studies have suggested that certain groups of athletes (especially soccer or American football players) may have an increased risk of ALS. Over the years, several studies tried to associate physical activity with the risk of developing ALS, leading to the hypothesis that the increased risk of ALS may be linked to factors related to sport rather than physical activity alone [75][76][77]. Indeed, recent studies evidenced that head impact exposure may increase the risk of neurodegenerative disease, in line with the observation that sports like soccer and football are those more linked to the development of ALS [78,79].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…[74] Previous studies have suggested that certain groups of athletes (especially soccer or American football players) may have an increased risk of ALS. Over the years, several studies tried to associate physical activity with the risk of developing ALS, leading to the hypothesis that the increased risk of ALS may be linked to factors related to sport rather than physical activity alone [75][76][77]. Indeed, recent studies evidenced that head impact exposure may increase the risk of neurodegenerative disease, in line with the observation that sports like soccer and football are those more linked to the development of ALS [78,79].…”
Section: Environmental Factorsmentioning
confidence: 99%